Primordial history, print capitalism, and egyptology in nineteenth-century Cairo - Mestyán, Ádám, 1979- (Le Caire)
vi, 129 sayfa, sayfa [133]-177 tıpkıbasım
Keywords: “How old is the world? This question was a central problem for Muslims, Christians, and Jews in the face of the new scientific discoveries in the nineteenth century. This book introduces the answer from a Muslim point of view, outside of official institutions. The extended introduction – a microhistory in the Middle East – explores the life and œuvre of a forgotten Egyptian intellectual and poet, Muṣṭafā Salāma al-Naǧǧārī (d. 1870). Next, Mestyan provides the English translation and Arabic transcription of the surviving fragments of al-Naǧǧārīʼs manuscript, The Garden of Ismail’s Praise. This is a universal history of Egypt, written while the Suez Canal was under construction to praise the governor Khedive Ismail (r. 1863-1879). The author advocates a unique solution to computing the period of primordial history, before the Deluge, in the age of steam and print. Al-Naǧǧārī's alternative Nahḍa voice is available for the first time in this edition“ --